INOVASI MANAJEMEN PERPUSTAKAAN MELALUI PROGRAM LITERASI POJOK BACA INSTAGRAMMABLE DI MTS NEGERI 7 BANYUWANGI - Galuh Prabowo (CV. ADIBA AISHA AMIRA, 2024)
This study examines and describes library management innovation through the Instagrammable reading corner program at MTsN 7 Banyuwangi. Researchers think that in every educational institution or agency there must be weaknesses or phenomena that need to be overcome, at MTsN 7 Banyuwangi the researchers found symptoms (obstacles) that could be examined, namely library management innovation through literacy in instagrammable reading corners. There is a problem regarding the lack of interest in reading students at MTsN 7 Banyuwangi which greatly affects the knowledge of students which is very sad. For this reason, researchers want to see more about library management that is used in the MTs Negeri 7 Banyuwangi library.The purpose of this study is to describe: 1) How is the implementation of library management in the MTsN 7 Banyuwangi library, 2) Knowing library management innovations, 3) Implementing a reading corner to increase student literacy. In this study the method used is descriptive qualitative method, which collects data through interviews, observation and documentation. In this research, we can find out the library management used to improve the reading literacy of MTsN 7 Banyuwangi students by using data analysis: 1) data reduction, 2) data presentation, 3) drawing conclusions and SWOT analysis.The results of the study show that 1) the implementation of library management at MTsN 7 Banyuwangi has operated in accordance with the POAC, 2) innovations in this library have succeeded in implementing the reading corner program, 3) after implementing this program students' interest in reading at MTsN 7 Banyuwangi has increased, and the program said to have been successful.